2009
DOI: 10.1098/rspb.2009.1926
|View full text |Cite
|
Sign up to set email alerts
|

Personality and collective decision-making in foraging herbivores

Abstract: The mechanisms by which group-living animals collectively exploit resources, and the role of individuals in group decisions, are central issues for understanding animal distribution patterns. We investigated the extent to which boldness and shyness affect the distribution of social herbivores across vegetation patches, using sheep as a model species. Using an experimental and a theoretical approach, we show that collective choices emerge through the nonlinear dynamics of interactions between individuals, at bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 69 publications
10
84
0
Order By: Relevance
“…Michelena et al 2010;Sibbald et al 2009), with it being shown that the boldness or shyness of individual sheep influences their grazing behaviours. Our set of results builds on this by indicating that sheep have temperament-related social preference for specific individuals within a flock; the temperament of both sheep within a pair, specifically their responsiveness in isolation, appears to be a factor driving social contact.…”
Section: Discussionmentioning
confidence: 99%
“…Michelena et al 2010;Sibbald et al 2009), with it being shown that the boldness or shyness of individual sheep influences their grazing behaviours. Our set of results builds on this by indicating that sheep have temperament-related social preference for specific individuals within a flock; the temperament of both sheep within a pair, specifically their responsiveness in isolation, appears to be a factor driving social contact.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than boldness correlating with leaderfollower relationships per se, high social transmission rates may have resulted from mixed groups containing both effective information producers-i.e., bold fish-along with shy individuals that may have been more likely to acquire social information and/or contributed to social conditions that facilitated transmission. Regardless of the mechanism(s) at work, these results are consistent with the idea that phenotypic diversity can facilitate flexible group-level responses to environmental challenges (Burns & Dyer, 2008;Michelena et al, 2010;Aplin et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…Conversely, within-group phenotypic diversity can facilitate flexible group-level responses to environmental variation (Burns & Dyer, 2008;Michelena et al, 2010) and can enhance group-level outcomes via synergistic interactions between phenotypic traits (Pruitt & Riechert, 2011;Aplin et al, 2014). As such, whether or not grouping is beneficial varies between individuals, across groups, and over time.…”
Section: Introductionmentioning
confidence: 99%
“…The personality's role in social dynamics remains largely unexplored [29,30]. Hence, the main objective of this study is to integrate personality into the study of aggregation dynamics and the related collective decision-making process in a group of cockroaches (Periplaneta americana).…”
Section: Introductionmentioning
confidence: 99%